The Usage of Dosing GAMA Application to Evaluate the Appropriateness of Drug Doses in Hospitalized Patients with Renal Impairment - Vidiya Gunarsih; Fita Rahmawati; Djoko Wahyono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
An application named ‘Dosing GAMA’ has developed for drug doses adjustment in patients with renal and hepar impairment. Dosing GAMA is targeted for clinical Pharmacists to calculate and make dose recommendations for patients, based on renal and hepatic conditions. This study aims to identify the appropriateness of drug dosage adjustment by using Dosing GAMA application in hospitalized patients with renal impairment and to determine the risk factors for the drug dose inappropriateness. This study was a retrospective observational descriptive study, cross-sectional design, used a consecutive sampling technique. The source of the data was Medical Record of hospitalized patients with renal impairment (creatinine clearance ≤50 mL/min) from 2018 of February till 2020 of March in the Academic Hospital of UGM. The names and the doses of the drugs were filled to Dosing GAMA application, and it would evaluate the appropriateness of drug doses. There were 570 drugs of 73 medical records included in this study. This study revealed Dosing GAMA could assess 144 drugs (25,6%) need to adjust, and 82 drugs (56,9%) were inappropriate doses. There were significant correlations of the age characteristic (p=0,000) and the creatinine clearance value (p=0,012) to the drugs dose appropriateness. There were inappropriate doses need to adjust in the hospital. So, the use of health-based technology expected for pharmacists to improve the use of drugs rationally.